1999
DOI: 10.1523/jneurosci.19-12-04921.1999
|View full text |Cite
|
Sign up to set email alerts
|

GABAAReceptor Subunit Composition and Functional Properties of ClChannels with Differential Sensitivity to Zolpidem in Embryonic Rat Hippocampal Cells

Abstract: Using flow cytometry in conjunction with a voltage-sensitive fluorescent indicator dye (oxonol), we have identified and separated embryonic hippocampal cells according to the sensitivity of their functionally expressed GABA A receptors to zolpidem. Immunocytochemical and RT-PCR analysis of sorted zolpidem-sensitive (ZS) and zolpidem-insensitive (ZI) subpopulations identified ZS cells as postmitotic, differentiating neurons expressing ␣2, ␣4, ␣5, ␤1, ␤2, ␤3, ␥1, ␥2, and ␥3 GABA A receptor subunits, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…Patch-clamp recordings made from embryonic and early postnatal cortical neurons show that they express functional GABA receptors that change properties significantly with development. GABA A receptors expressed in proliferating precursors have higher apparent affinity, long channel kinetics (491), and long channel open times in neuroepithelial cells (414). The different properties of GABA A receptors are most likely due to different subunit composition, although other factors play an important role including intracellular calcium concentration, degree of receptor phosphorylation, association with anchoring proteins, and degree of clustering of the receptors.…”
Section: Gaba Influences Dna Synthesis In Precursor Neocortical Cellsmentioning
confidence: 99%
“…Patch-clamp recordings made from embryonic and early postnatal cortical neurons show that they express functional GABA receptors that change properties significantly with development. GABA A receptors expressed in proliferating precursors have higher apparent affinity, long channel kinetics (491), and long channel open times in neuroepithelial cells (414). The different properties of GABA A receptors are most likely due to different subunit composition, although other factors play an important role including intracellular calcium concentration, degree of receptor phosphorylation, association with anchoring proteins, and degree of clustering of the receptors.…”
Section: Gaba Influences Dna Synthesis In Precursor Neocortical Cellsmentioning
confidence: 99%
“…Embryonic hippocampal neuronal cultures include a heterogeneous mixture of pyramidal and nonpyramidal neurons of multiple different morphologies (Rothman and Cowan, 1981). The cultured cells express GABA A R subunits ␣1-␣5, ␤1-␤3, ␥1-␥3 and ␦ (Brooks-Kayal et al, 1998;Maric et al, 1999).…”
Section: E In Vitro Models To Study Regulation Of Gaba a Receptor Exmentioning
confidence: 99%
“…The next step was to include the singly bound open and desensitized states in the scheme postulating two identical and independent binding sites. An estimation of the rate constants (␣ 1 , ␤ 1 ) for partially liganded open states was based on the evidence from single channel analysis (Macdonald et al 1989;Twyman et al 1990), as well as on assessments made in similar models (e.g., Jones and Westbrook 1995;Maric et al 1999). In all these studies, the rate constant of entrance into the singly bound state (␤ 1 ) has been found to be much slower than that leading into the fully bound state (␤ 2 ), and the rate of return into the closed state (␣ 1 ) was fast.…”
Section: C-g)mentioning
confidence: 99%